Influence of pre-torsion angles on torsion fatigue properties of 45CrMoVA steel bars. (August 2020) - Chen, J.Z.; Zhang, B.; Song, Z.M.; Wan, H.Y.; Zhang, G.P.
Graphical abstract: Highlights: Torsion fatigue properties of pre-twisted 45CrMoVA steel specimens were investigated. Torsion fatigue fracture mechanism of the pre-twisted specimens was elucidated. A model for the torsion fatigue life of pre-torsion specimens was established. The desired pre-torsion angle was obtained for maximizing torsion fatigue life. Abstract: 45CrMoVA steel bar specimens were pre-twisted at different angles ( θ pre ) ranging from 8.3° to 16.3°. Torsion fatigue properties of the pre-torsion specimens were investigated. The results indicate that the torsion fatigue life of the specimens increases first, and then decreases with increasing θ pre . A model was established to predict torsion fatigue life for the pre-torsion shaft components, and the desired θ pre of 11.4° corresponding to the longest fatigue life for the pre-torsion 45CrMoVA steel bars was obtained. It is expected that the model may provide a guideline for the pre-torsion process of the steel shaft parts.